The Effect of Centella asiatica Cream on Transforming Growth Factor Beta 1 in Acute Wounds - Ulfa, Maria; Iskandar, Elza; Erna, Riani; Saleh, M Irsan (Fakultas Kedokteran Universitas Brawijaya, 2026)
Centella asiatica contains triterpenoids with anti-inflammatory, antioxidant, and antifibrotic properties and has long been used in wound healing. Previous studies suggest that Centella asiatica may reduce TGF-β1 expression, which is implicated in scar and keloid formation. Given the pleiotropic role of TGF-β in wound healing being required in the inflammatory phase and downregulated during proliferation this study employed an acute wound model to represent normal healing and to evaluate the effect of Centella asiatica extract on TGF-β1 expression. This study aimed to evaluate the effects of topical Centella asiatica cream application at concentrations of 0.5%, 1%, and 2% on TGF-β1 levels in acute wound healing in Wistar rats. An experimental posttest-only control group design was conducted at the Pharmacology Laboratory, Animal House, and Biotechnology Laboratory, Faculty of Medicine, Universitas Sriwijaya. Five groups were studied, consisting of one untreated group, three groups treated with Centella asiatica cream at concentrations of 0.5%, 1%, and 2%, respectively, and one group treated with placebo, with five rats in each group. Data were analyzed using One-way ANOVA, and Post Hoc LSD tests. Results showed the highest TGF-β1 levels in the placebo group and the lowest in the 1% Centella asiatica cream group. Significant differences were found between the 1% Centella asiatica cream group and the untreated (p=0.026), placebo, and 2% Centella asiatica cream groups (p=0.008). In conclusion, the Centella asiatica cream concentration of 1% was the most effective in reducing TGF-β1 levels in acute eyelid wound healing in Wistar rats.